Dual‐photon microscopy‐based quantitation of fibrosis‐related parameters (q‐FP) to model disease progression in steatohepatitis. Issue 6 (28th April 2017) - Wang, Yan; Vincent, Robert; Yang, Jinlian; Asgharpour, Amon; Liang, Xieer; Idowu, Michael O.; Contos, Melissa J.; Daitya, Kalyani; Siddiqui, Mohammed S.; Mirshahi, Faridoddin; Sanyal, Arun J.
Abstract : There is a need for further refinement of current histological systems for assessment of hepatic fibrosis in nonalcoholic fatty liver disease (NAFLD). This study evaluated hepatic fibrosis in NAFLD using dual‐photon microscopy‐based quantitation of fibrosis‐related parameters (q‐FPs). Fifty test cohort subjects and 42 validation cohort subjects with NAFLD and the full spectrum of fibrosis were studied. q‐FPs were measured in specific predefined regions of interest (general, vessel, perisinusoid, and vascular septa). Seventy q‐FPs had inter‐ and intraobserver concordance ≥0.8 and were related to the NASH Clinical Research Network fibrosis staging. Of these, 16 q‐FPs with the strongest correlations ( P < 0.001 for all) were entered in a principal component analysis model (odds ratio [OR] 7.8, P < 0.001), which separated any stage of fibrosis versus no fibrosis, and cirrhosis versus earlier stages with the areas under the receiver operating characteristic curves of 0.88 and 0.93 ( P ≤ 0.01 for both), respectively. In an independent multivariable analysis, four q‐FPs—the number of collagen strands (OR 8.5, P = 0.004), strand length (OR 12.0, P = 0.02), strand eccentricity (OR 8.3, P = 0.004), and strand solidity (OR 8.0, P = 0.003)—were independently associated with fibrosis stages and were used to model fibrosis along a continuous linear scale using desirability functions; this linear scale of fibrosis measurement was also related to fibrosis stage ( P < 0.0001). The robustness of both the multivariable model and the linear scale of measurement was confirmed in the validation cohort. Conclusion : The q‐FP model provides an accurate reproducible method to evaluate fibrosis in NAFLD along a quantitative and continuous scale. (Hepatology 2017;65:1891‐1903).